La documentación epigráfica cristiana de Mértola: su datación - Santiago Fernández, Javier de (Revista General de Información y Documentación, 2003)
The present article offers a chronological study of three inscriptions from the Lusitanian city of Mértola. The method is based on the study both of external elements, especially the evolution of decoration and writing, and of internal elements, fundamentally the evolution of expressions and idioms used in the epitaphs.